Respiratory microbiota, host immunity, respiratory viral infections and malignant tumors - Jiang, Xinjie; Zhang, Sujiang (Frontiers in Microbiology, 2025)
In recent years, the role of the respiratory tract microbiota in respiratory tract infections has attracted considerable attention. Respiratory microbiota have important effects on respiratory physiology, immune regulation, and the occurrence and development of various respiratory viral infectious diseases. The microbial composition in the different parts of the respiratory tract, such as the nose, oropharynx, and lower respiratory tract, varies. Under physiological conditions, the respiratory microbiota remains relatively stable; however, when this homeostatic balance is disrupted, respiratory microbiota imbalance occurs, increasing the risk of infection. An increasing number of studies have revealed the complex relationship between bacterial dysregulation and respiratory viral infections. Dysregulation of the respiratory tract microbiota plays an important role in both innate and adaptive immune responses. In this study, changes in respiratory microbes and their interactions with host immunity, respiratory viral infections and malignant tumors were reviewed. Future studies should further explore the interaction mechanism between respiratory microbiota and host immunity, develop new diagnostic and therapeutic strategies, and improve the current level of clinical treatment for respiratory diseases.